Guidelines for Fiscal Adjustment - Davis, Jeffrey (Pamphlet Series; Pamphlet Series, ;, 1995)
This pamphlet considers some of the issues and concerns that underlie the IMF's approach to fiscal adjustment-namely, the ways governments can use their fiscal stabilization and structural policies to achieve macroeconomic objectives relating to growth, inflation, and the balance of payments. It covers such issues as government taxing, spending, and borrowing, as well as some fiscal aspects of institutional change, and offers practical policy options for consideration.